Whirl Pattern Complex Gastroschisis - Andrés Felipe Rubio Duarte; Mónica Beltrán-Avendaño; Daniella Chacón-Valenzuela (Mashhad University of Medical Sciences, 2024)
Background: Complex gastroschisis is a rare variant characterized by intrauterine closure of the abdominal defect, which can be accompanied by atresia, necrosis, and, in most cases, lead to short bowel syndrome. This is the first case of gastroschisis presenting as a whirl pattern of loops and raises suspicion of intestinal ischemia and atresia. Case Report: A newborn at 38 weeks of gestation with a prenatal diagnosis of complex gastroschisis presented with a whirl pattern of gastroschisis and jejunal atresia. The newborn was treated with staged closure of the defect and underwent a second surgical procedure for correction of jejunal atresia, with a successful outcome observed during 2 years of follow-up. Conclusion: Whirl pattern gastroschisis is a rare presentation of complex gastroschisis, and its diagnosis can be made prenatally, allowing for the preparation of medical and surgical management at birth. It is necessary to actively search for the presence of intestinal atresia or ischemia in this type of presentation.